MUTUAL RESPECT BEHAVIOR IN THE GREATEST SHOWMAN MOVIE DIRECTED BY MICHAEL GRACEY (2017) A SOCIOLOGICAL APPROACH - Nugroho, Febrianto Agung (Jurusan Sastra Indonesia, 2024)
This study aims to identify how social behavior respects each other in the film The Greatest Showman directed by Michael Gracey and released in 2017. This research is a qualitative research with a focus on analyzing the behavior and interactions of each character in respecting other characters and how the impact of mutual rsespect that occurs in each character. The technique used in this research is descriptive analysis. From this research, several problem formulations were found. First, how the occurrence of mutual respect. Second, what is the impact of mutual respect between characters. Third, how is the comparison of mutual respect in movies and in everyday life. Mutual respect, Compassion, Love and empathy are words that everyone agrees have a positive meaning. However there are many theories about what respect means. Perhaps the reason it is so difficult to define is that it can mean different things to different people depending on whether it is used as a verb or as a noun depending on the cultural background and context in which it is discussed.KEY WORDS : The Greatest Showman, Sociological Approach, Mutual Respect